An investigation into linguistic features of articles introducing traditional musical instruments in english and vietnamese - Nguyễn,Thị Minh Tâm (ĐHĐN., 2015)
The thesis primarily aims at carrying out an investigation of ATMIEs and ATMIVs in order to find out their syntactic features, lexical features and the employment of stylistic devices. The paper design is based on a combination of both qualitative and quantitative approaches. The qualitative method is used to describe and analyze data to find out the similarities and differences between ATMIEs and ATMIVs in terms of syntactic features, lexical features and stylistic devices and then determine the frequency of occurrence and the percentage of them. In addition, the data for this study is 40 samples for English and Vietnamese Articles gathered from websites on internet. Lastly, the findings of the study will provide the Vietnamese teachers with some basic background knowledge of linguistic features of ATMIs in English and Vietnamese such as syntax, a lexical and stylistic devices. The findings have more important implications for teaching language skills especially, teaching writing skills for the students majoring English.